Tratamento anaeróbio de efluente de abatedouro de aves utilizando surfactina produzida em manipueira - Cosmann, Natássia Jersak (2015)
The effluent from poultry slaughterhouse has high concentration of organic matter, thus, it is essential to carry out a treatment before being disposed in the environment. A physico-chemical pretreatment is usually put forward mostly in order to remove fat. Recently, the addition of microbial metabolites, which act out to emulsify or break down fats, is studied as an alternative pre-treatment. The biosurfactants are metabolic products from several microorganisms and can solubilize and emulsify a solution composed of two immiscible liquids; thereby it promotes greater availability of components responsible for biodegradation. In this regard, this study aimed at evaluating the anaerobic treatment of effluent from poultry slaughterhouse when using surfactin produced in cassava. The obtained biosurfactant was characterized by High Performance Liquid Chromatography (HPLC) as surfactin in 30% crude extract concentration, with excellent emulsifying properties, emulsion stability of hydrocarbons and green oils, so that Critical Micelle Concentration (CMC) was 28 mg. L-1. It was also observed, according to the methodology of specific methanogenic activity (SMA), that surfactin did not inhibit microbial community present in sludge to be used as inoculum during the anaerobic biodigestion. It was also registered that methane production and reduction of Soluble Chemical Oxygen Demand (SCOD) was very similar among the applied treatments. Pretreatment of effluent from poultry slaughterhouse with the produced surfactin was carried out under the following conditions: 150 mL working volume, 150 rpm stirring and the incubation time of six hours. The effects of temperature variables (25, 30, 42.5, 55 and 60 ° C) and surfactin concentration (6, 13.27, 31, 48.73 and 56 mg.L-1) on SCOD increase were evaluated by the method of delineation Central Composite Rotational (DCCR). It was observed that the 4.5-hour time was enough to solubilize COD at its maximum concentration and at higher temperatures and concentrations of surfactin (above CMC), the greatest values of increase were reached in COD solubility. The anaerobic treatment of pretreated effluents under the aforementioned conditions was developed based on the following conditions: 34 °C without stirring, with eudiometers to check methane production and with destructive samples for temporal analysis of physico-chemical parameters. Microbiological analysis of anaerobic sludge was carried out for initial and final inoculum characterization among treatments according to the methodologies of Fluorescent In Situ Hybridization (FISH) and Gram stain. It was observed that effluent from poultry slaughterhouse can be submitted to anaerobic digestion, methane production in biogas. The cumulative volume of methane at the end of the trial for the control treatment, in which there was no surfactin addition in the pretreatment, was the lowest observed among the treatments. SCOD removal was the same among the studied treatments as well as the removal of oils and greases (GL), which may have been provided with the temperature effect on the effluent constituents rather than a direct action in phase of biosurfactant pretreatment. The assays monitoring through destructive samples allowed observing a temporal behavior of the control parameters directly involved in anaerobic digestion and note that the process developed properly. From the microbiological analyses, it was observed that the biosurfactant surfactin did not inhibit the emergence of bacterial genera commonly present in anaerobic wastewater treatment and presented in all treatments a great number of microbial species. In general, it can be inferred that the biosurfactant surfactin did not significantly change any of the poultry slaughterhouse effluent properties, which allow improvements in anaerobic biodegradation and consequent increased production of methane.